MESIN TRESHER PADI OTOMATIS - Riady, Herwin; Nurhuda, Ahmad; Akbar, Sari Ametrina; Fitria, Liana Agus (Program Kreativitas Mahasiswa - Teknologi, 2014)
West Sumatra is Indonesias rice granary areas whose production is more than 2 million tons per year, the county / city pariaman fields whose production is more than 300 thousand tons per year. Constraints faced by farmers who continually was never resolved during the post-harvest rice, as the process is still done traditionally, that is by hitting the rice stem kedinding mairik bamboo and rice. In this way a lot of rice is wasted, labor intensive and it takes a long time. Although there have been tresher rice machine but not working optimally and power capacity is also small. Also the price is more expensive than 12.5 million dollars. This activity aims to design a machine wake of appropriate technology, automatic rice tresher machine "to improve the quality of post-harvest rice quickly and quality". PKM-T program activities include reviewing, planning / engineering, strengthening the design, manufacture key components of automated rice tresher machine and testing machine design results and preparing reports. This machine is capable of removing the rice 2-fold compared to the old machine that is 2 acres tresher within 4-5 hours per day. So as to increase the income of farmers more than 19.2 million dollars.Keyword: rice and rice tresher automatic machine